2018
DOI: 10.1111/hex.12839
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the processes of change and engagement from using a social network intervention for people with long‐term conditions. A qualitative study

Abstract: Background Personal and community networks are recognized as influencing and shaping self‐management activities and practices. An acceptable intervention which facilitates self‐management by mobilizing network support and improves network engagement has a positive impact on health and quality of life. This study aims to identify the processes through which such changes and engagement take place. Methods The study was conducted in the south of England in 2016‐2017 and adopted a longitudinal case study of networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…It has been found that CoP is a powerful mechanism for solving problems ( 22 ). Mobilizing the capability of a group working together can be a useful pathway to support changes because it highlights the process of engagement with the current concerns of individuals and the group members ( 7 ). These point to the results showing that sharing experiences can lead to patients gaining an increased understanding of their health condition and how it affects everyday life, leading to the feeling of empowerment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that CoP is a powerful mechanism for solving problems ( 22 ). Mobilizing the capability of a group working together can be a useful pathway to support changes because it highlights the process of engagement with the current concerns of individuals and the group members ( 7 ). These point to the results showing that sharing experiences can lead to patients gaining an increased understanding of their health condition and how it affects everyday life, leading to the feeling of empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…This perspective is missing when providers take the lead in self-management programs ( 5 ). Bringing a social environmental dimension to self-management support by providing socially based options to improve health and well-being has shown to be successful ( 6 , 7 ). This social dimension is based on deepening relationships within personal communities of support—such as personal networks—that link both social activities and the management of health and well-being of the members of the community ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…These topics mirrored those of the top 6 life and health goals identified by older adults in another study conducted in Ontario [ 32 ]. Furthermore, GENIE studies conducted in the United Kingdom also showed that most activities chosen in other related GENIE studies also tended to be health related [ 26 , 27 ]. This provides support that the topics in the GENIE tool are relevant to an adult population.…”
Section: Discussionmentioning
confidence: 99%
“…GENIE is a web-based tool that aims to support self-management by leveraging adults’ engagement with their personal social network to facilitate the uptake of relevant community-based activities and HSSs. Studies have shown that when GENIE was delivered by trained facilitators to adults with chronic health and social conditions in the community settings, there was an increase in the diversity of participants’ networks and greater engagement with community activities [ 26 , 27 ]. Given these positive results and the challenges faced by primary care providers in implementing self-management strategies [ 17 ], research is needed to understand the feasibility, usability, and perceived impacts of implementing GENIE within the primary context, with the use of trained facilitators as an extension of the primary care team.…”
Section: Introductionmentioning
confidence: 99%
“…This shift aligns with the succinct idea that people do “self-manage” their conditions, but they do not self-manage on their own (Vassilev et al, 2013). This new direction has opened up a space for medical sociology with an emphasis on understanding the role that social networks play in helping patients to live well with their condition (Morris et al, 2016; Vassilev et al, 2019).…”
Section: Introductionmentioning
confidence: 99%